Effect of Selenium and Vitamin E Supplementation on Immune Indicators, Antibody Response, and Antioxidant Status in Sheep: Development of an Immunocompetence Index (Indian Journal of Animal Production and Management, 2025)
Background: Selenium (Se) and vitamin E are essential micronutrients with synergistic antioxidant and immunomodulatory functions. In selenium deficient regions, supplementation may enhance immune function and vaccine efficacy in small ruminants. Objective: This study aimed to evaluate the effects of Se, vitamin E, and their combination on cellular and humoral immunity, cytokine profiles, antioxidant status, vaccine response, and develop an Immunocompetence Index (ICI) for health assessment. Methods: One hundred twenty Awassi sheep (6 months old, 28±3 kg, both sexes equally distributed) from a selenium-deficient region were allocated to four groups for 90 days: Control, Se (0.3 mg/kg DM as sodium selenite), Vit E (250 IU/day dl-α-tocopherol), and Se+Vit E (combined). Blood samples were analyzed for cellular immunity (lymphocyte subsets by flow cytometry, phagocytic activity, proliferation), humoral immunity (IgG, IgM, IgA), cytokines (IL-2, IL-4, IL-6, IL-10, IFN-γ, TNF-α), antioxidant status (Se, GPx, SOD, TAC, MDA), and antibody response to FMD and PPR vaccines. Health status was monitored throughout. ROC analysis was performed. Results: Baseline values confirmed selenium deficiency (Se 68.4 ng/mL) and did not differ among groups (P > 0.05). At Day 90, Se+Vit E significantly enhanced (P < 0.05) cellular immunity: CD4+ T cells (24.6 → 36.8%, +50%), phagocytic activity (42.6 → 68.4%, +60%), lymphocyte proliferation index (1.86 → 3.42, +84%). Humoral immunity improved: IgG (12.4 → 18.6 mg/mL, +50%). Antioxidant status enhanced: GPx (186 → 325 U/L, +74%), while MDA decreased 57%. FMD antibody titers increased 3.2-fold. No clinical signs of toxicity were observed. GPx showed strongest predictive performance (AUC = 0.94). The proposed ICI achieved 92.4% accuracy. Conclusion: Combined Se+Vit E supplementation synergistically enhances immunity and vaccine response in selenium-deficient sheep. The ICI provides a practical tool for assessing immunocompetence.
Keywords: Selenium; vitamin E; immune function; antibody response; antioxidant; Awassi sheep; vaccination